A study of the level of awareness on the distribution of property according to Islamic faraid law: a case study among clients of the Kuantan Syariah court / Shahrul Anuar Marzuki - Marzuki, Shahrul Anuar (2018)
This study examines the factors of awareness among Muslims on the distribution of inheritance according to the laws of Faraid. Facts are science, mass media, and obedience to religion. Where this study identifies whether these factors have a positive impact on the division of Faraid property. This study covers faraid and his application in Kuantan Pahang, in theory and practical. Faraid is the law of inheritance and is the subject of the most detailed legal provisions in the Quran. Because of his importance Rasulullah urged his companions to acquire certain knowledge and warn them that Faraid knowledge or inheritance knowledge. Because faraid means obligations, many consider it a mandatory law, for which Muslims have no choice but to comply. The study, however, concludes that it is not an obligation for Muslims to dispose of their inheritance according to the prescribed property in the Qur'an. The respondents of this study were clients of faraid applications in kuantan shariah courts. The research instrument used is a self-built questionnaire and consists of 20 question' items. Researchers have used the Statistical Package for Social Science version 20 (SPSS) to analyze raw data for frequency, percentage, mean and correlation. The findings as a whole show that the factor of consciousness among Muslims on the distribution of estate according to faraid is at a high level. While the level of understanding of the respondents to faraid knowledge is at a simple stage. At the end of the study, several suggestions have been proposed to raise the level of knowledge and understanding among Muslims.